Efficacy and safety of lenvatinib in a case of thymic carcinoma complicated with interstitial lung disease and anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis: A case report - Yuki Hatakeyama; Jun Sakakibara-Konishi; Masato Tarumi; Kosuke Tsuji; Hirofumi Takahashi; Megumi Furuta; Yuta Takashima; Hidenori Kitai; Tetsuaki Shoji; Yasuyuki Ikezawa; Satoshi Konno (Respiratory Medicine Case Reports)
Based on the results of a multicenter phase II study of patients with previously treated thymic carcinoma, lenvatinib administration for unresectable thymic cancer has been covered under insurance in Japan since 2021. However, patients with interstitial lung disease (ILD) were excluded from that study; therefore, the efficacy and safety of lenvatinib in these patients remain unknown. Herein, we report the case of a woman in her 50s who was diagnosed with thymic carcinoma complicated with ILD. In August 2016, the patient developed ILD with anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive dermatomyositis (DM). She received triple therapy comprising prednisolone, tacrolimus and azathioprine. In October 2021, the patient complained of lateral chest pain and back pain. In January 2022, computed tomography (CT) revealed an anterior mediastinal tumor, and percutaneous biopsy resulted in a diagnosis of thymic carcinoma with Masaoka classification IVb. In March 2022, first-line treatment with four cycles of carboplatin (area under the curve, 6) + paclitaxel (200 mg/m2) was initiated. Although a partial response was achieved, in September 2022, CT demonstrated progressive disease (PD). Therefore, in October 2022, Lenvatinib (24 mg) was started as the second-line treatment. The best response was stable disease; moreover, although lenvatinib dose reduction was required owing to adverse events, such as biliary-tract infection and stomatitis. The patient did not experience ILD exacerbation. Lenvatinib (14 mg) was continued until PD was observed in March 2023. Our findings suggest that lenvatinib is a viable treatment option for thymic carcinoma with ILD.